Pendidikan Teman Sebaya (Peer Education) sebagai Upaya Pencegahan Perdagangan Manusia - Muhamad Tisna Nugraha (PSGA LP2M IAIN Pontianak, 2019)
Human trafficking has globally become the problems which is passed through border area in some countries. The crime does not merely have an impact on social aspects, but also on other aspects such as politics, social, and culture. Therefore, no wonder that the human trafficking case is on the top five of hugest crimes in the world. Then, it is really difficult to wipe out. Furthermore, the efforts to eradicate human trafficking have been undertaken on many ways. One of them is to enforce the strict laws for perpetrators. Nevertheless, this action has been considered ineffective to lessen the human trafficking case, even for some cases, this crime develops more. Moreover, the new model of slavery is still occured and has an effect on Human Rights cases. Therefore, peer education could be one of alternative solutions to fight for human trafficking. It is one of approaches in education using peer groups to educate and share information related to human trafficking.